Synchronous presentation of muscle-invasive urothelial carcinoma of bladder and peritoneal malign mesothelioma - Basatac,Cem (2019)
ABSTRACT Introduction Cancer is one of the most important leading cause of death in man and woman in the world. The occurrence of new cancer has become more frequent in recent years due to strict screening protocols and occupational and environmental exposure to carcinogens. The incidence of secondary malignancies has also increased due to close medical follow-up and advanced age. Herein, we report a case and its management diagnosed as synchronous peritoneal malignant mesothelioma and muscle-invasive urothelial carcinoma. Case Description A 71-year-old male presented with macroscopic hematuria and abdominal distension increasing gradually. A contrast enhanced computerized tomography demonstrated bladder mass and diffuse ascites with nodular peritoneal thickening and umbilical mass. He was treated with the multidisciplinary team working including urologist, medical oncologist and general surgeon. Conclusions To our knowledge, this is the first case of peritoneal malign mesothelioma with synchronous muscle-invasive urothelial carcinoma. Because of the rarity of this condition, there is still no consensus on the definitive treatment protocols, yet. Individualized treatment with multidisciplinary close follow-up might improve the survival outcomes.